Twisted large cellular fibroma of the ovary with pelvic effusion-revisiting incomplete demons Meigs’ syndrome - T., Heera Shenoy; Antony, Abhilash; Kailash, Nishi; P., Shameema; P., Sathi P.; N., Fazna; Khader, Reslin; R., Rajendran V.; K., Thara Thomas; Jayakumar, Jayakrishnan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Fibromas of the ovary are benign tumours arising from the stromal component of the ovary. They represent 1% of ovarian neoplasms and are generally benign. The cellular subtype accounts for around 10% of these and is a tumour of uncertain malignant potential. Recurrence may occur or it could be associated with peritoneal implants. Usually these are solid tumours, sometimes with small areas of cystic degeneration. Occasionally, large fibromas may undergo torsion causing acute abdominal pain and generally tends to occur in post-menopausal women. The solid areas, ORADS and ascites simulated a malignant ovarian tumour on both MRI, USG and gross pathologic examination. Here we present a case of a postmenopausal woman presented with abdominal pain and postprandial vomiting with a large twisted ovarian fibroma leading to diagnostic and therapeutic challenges masquerading as a malignant ovarian neoplasm.